2020
DOI: 10.1177/1053815120921946
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function in Infants and Toddlers Born Low Birth Weight and Preterm

Abstract: Infants born low birth weight (LBW) and preterm were evaluated in a high-risk follow-up clinic and compared with infants born full term. A multivariate linear model was used to examine the overall differences on Bayley Scales of Infant Toddler Development (BSID-III) among three groups: full term, heavy LBW (<2,500 g ≥2,000 g), light LBW (<2,000 g). Results indicated no significant differences in BSID-III scores between the groups. The BSID-III was used to extrapolate indicators of executive function (EF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Multivariate analyses of score differences revealed that infants born with VLBW scored lower than their peers with heavier birth weights on both the DMQ18 negative reaction to challenge—frustration/anger and all scales of the BSID-III except the expressive language subscale. This finding is not surprising, as there is low item density for expressive language on the BSID-III, especially during the infant years ( Blasco et al 2020 ). The mean age of infants included in this study was 10 months.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Multivariate analyses of score differences revealed that infants born with VLBW scored lower than their peers with heavier birth weights on both the DMQ18 negative reaction to challenge—frustration/anger and all scales of the BSID-III except the expressive language subscale. This finding is not surprising, as there is low item density for expressive language on the BSID-III, especially during the infant years ( Blasco et al 2020 ). The mean age of infants included in this study was 10 months.…”
Section: Discussionmentioning
confidence: 84%
“…There have been long-standing concerns that the BSID-III provides higher-than-anticipated scores when correcting for prematurity (Anderson et al 2010;Duncan et al 2015;Hack et al 2005). In a later study, Blasco et al (2020) found no differences in BSID-III scores for 6-month-olds born with LBW and between preterm and full-term peers. However, differences were noted in DMQ18 cognitive and social persistence.…”
Section: Limitationsmentioning
confidence: 91%
See 2 more Smart Citations